COVID-19 in solid organ transplant recipients after 2 years of pandemic: Outcome and impact of antiviral treatments in a single-center study - Pinchera, Biagio; Buonomo, Antonio Riccardo; Trucillo, Emilia; Susini, Stefano; D’Agostino, Alessia; Di Filippo, Isabella; Tanzillo, Anastasia; Villari, Riccardo; Carrano, Rosa; Troisi, Roberto Ivan; Gentile, Ivan (Frontiers in Transplantation, 2023)
More than two years after the pandemic, the availability of vaccination and the use of monoclonal antibodies and direct antivirals have changed the fate of COVID-19, allowing for a better management of the disease, reducing hospitalization rates, and improving survival. This real-life study aims to describe the outcome of COVID-19 in a cohort of solid organ transplant recepients and the impact of novel antivirals against SARS-CoV-2. We conducted an observational retrospective cohort study. We enrolled solid organ transplant recipients with COVID-19 attending the A.O.U. Federico II of Naples and followed up from January 2022 to July 2022. We enrolled 40 SOTs with COVID-19. Our real-life experience highlights the favorable impact of therapies with antivirals and monoclonal antibodies in the early stages of COVID-19. Interesting data concern the impact of immunosuppressive therapy on COVID-19, in particular the role of Mycophenolate (associated with deterioration to severe COVID-19) and Everolimus (protective for progression to severe disease) needs to be investigated. Our experience also confirms the fundamental role of vaccination and in particular the importance of the boster dose.